Tumbleweeds : [a novel] - Meacham, Leila, 1938- (Hachette Audio, 2012)
Tumbleweeds is the story of three young friends, the saint, the sinner, and the angel, growing up together in the sort of small Texas Panhandle town that lives and dies by its Friday night football games. A fateful event casts a long shadow over these three intertwined lives and leaves the listener desperate to see how it all plays out.